2016
DOI: 10.4097/kjae.2016.69.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Simply modified percutaneous tracheostomy using the Cook® Ciaglia Blue Rhino™: a case series

Abstract: When first introduced, percutaneous dilatational tracheostomy (PDT) was performed using a bronchoscope. The bronchoscope itself, however, has several disadvantages, including interruption of ventilation. Modifications of the standard PDT technique have suggested that PDT can be safely performed without a bronchoscope. However, the safety of these modifications is unclear and many modifications have yet to be widely adopted. This study retrospectively evaluated the safety of a simplified PDT technique using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…Some of the researchers have mentioned that more than 250 mL of bleeding during PCDT should be regarded as severe bleeding. 15 In our study, mean blood loss in group-M was lesser than the FOB-guided group but it was not clinically significant [although statistically significant ( p = 0.001)]. Maximum bleeding documented in our study was 15 mL in both the study groups.…”
Section: Discussioncontrasting
confidence: 46%
“…Some of the researchers have mentioned that more than 250 mL of bleeding during PCDT should be regarded as severe bleeding. 15 In our study, mean blood loss in group-M was lesser than the FOB-guided group but it was not clinically significant [although statistically significant ( p = 0.001)]. Maximum bleeding documented in our study was 15 mL in both the study groups.…”
Section: Discussioncontrasting
confidence: 46%
“…PDT was performed using Ciaglia Blue Rhino ™ [4] ; the technique is herein described. Firstly, cannula's cuff capacity is checked to reduce the risk of cuff's rupture.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that PDT was safely performed 2 cm below the cricothyroid membrane without bronchoscopy in 186 patients by confirming the underlying structures through palpation [10]. Although this simplified method is convenient and does not require sophisticated equipment, its biggest drawback was the inability to confirm the precise location for PDT, which is critical when performing PDT [11,12].…”
Section: Introductionmentioning
confidence: 99%